Implementation of the RAD Method in the Design and Development of the Melati Library Information System Tebat Agung Village Web-Based - Davena Nola; Ariansyah; Jepri Yandi (Yayasan Kita Menulis, 2026)
The development of information technology offers solutions for library management, including at Melati Library in Tebat Agung Village, Muara Enim Regency, South Sumatra, which still uses a manual system. Issues include recording, book borrowing and returning, searching, and report generation, all of which are inefficient. This study aims to design a web-based library information system using the Rapid Application Development (RAD) method, which enables fast and structured system development. The system was developed using a descriptive qualitative approach, UML modeling, PHP programming language, and MySQL database. The resulting system simplifies book data management and is expected to improve the efficiency and quality of library services overall.